Optimal Planned Electricity Allocation Model for Power Exchange Under the Plan-Market Double-Track Mechanism - He, Chuan; Tang, Jiajun; Zhang, Weishi; Zhang, Zhi; Lin, Zhemin; Li, Yating; Qian, Hanhan; Jiang, Hailong; Lin, Zhenzhi; Yang, Li (Frontiers in Energy Research, 2021)
The orderly deregulation of planned electricity generation and consumption is an important measure for electricity market reform in several countries (such as China), and a reasonable proportion of planned electricity in the total energy consumption is conducive to the smooth transition from the regulation mode to the market mode. Under the plan-market double-track mechanism (PMDM) implemented, a modified linear bidding function of generation companies (GCs) is first proposed, and the unified clearing price of unilateral generation market is determined accordingly. Second, considering the robust bidding strategies of generation companies, a bi-level optimal planned electricity allocation model for power exchange (PX) is constructed. In the upper level, the proportion of planned electricity is optimized by PX to minimize the CVaR of Lerner Index (LI), so as to maintain the market power at a low level. In the lower level, based on the robust optimization theory and the prediction of rival bidding, the bidding strategy of a GC is optimized by solving a specified max–min problem. Simulations based on data from a provincial electricity market in China illustrate that the market power can be reduced through a reasonable proportion of planned electricity designed by the PX. In addition, when more GCs tend to avoid a market risk, the proportion of planned electricity can be increased accordingly.